2002
DOI: 10.1055/s-2002-34495
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Alexander Disease: AGFAPMutation in Monozygotic Twins and Novel Mutations in Two Other Patients

Abstract: Alexander disease (AD) is a rare disorder of cerebral white matter due to a dysfunction of astrocytes. The most common infantile form presents as a megalencephalic leukodystrophy. Recently, heterozygous de novo mutations in the glial fibrillary acidic protein gene (GFAP) have been demonstrated to be associated with AD. We report heterozygous mutations in GFAP in 5 patients, including a pair of monozygotic twins, with clinical and neuroradiological features of infantile AD. Novel mutations were detected affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…The R79H mutation identified in our patient is common in the USA and European populations with the infantile form of AD [4][5][6][7], but our patient did not present with the typical clinical signs of the infantile form such as megalencephaly, developmental deterioration, and seizures from early infancy. The white matter lesions detected in our patient by MRI were not as extensive as lesions previously reported in patients with this mutation [4,7]. In addition, we did not detect widespread damage of white matter upon analysis of somatosensory evoked potentials (normal central conduction time).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The R79H mutation identified in our patient is common in the USA and European populations with the infantile form of AD [4][5][6][7], but our patient did not present with the typical clinical signs of the infantile form such as megalencephaly, developmental deterioration, and seizures from early infancy. The white matter lesions detected in our patient by MRI were not as extensive as lesions previously reported in patients with this mutation [4,7]. In addition, we did not detect widespread damage of white matter upon analysis of somatosensory evoked potentials (normal central conduction time).…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, the distinction between the infantile and juvenile forms is not clear. Mutations in the GFAP gene have recently been identified in AD patients [3], and phenotypic variation between cases has been documented [4][5][6][7][8][9]. However, genotype-phenotype correlations…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from blood leukocytes by standard methods. Mutation analysis was performed as described earlier [16]. Basically, the complete coding exons of the GFAP gene were amplified by polymerase chain reaction (PCR), which was carried out in 50-µl reactions with 100 ng of patient DNA, 20 pmol of each primer, 25 µl of HotStar Taq master mix (Qiagen) in water, using the following PCR protocol (95°C for 15 min; 35 cycles at 95°C for 20 s, 56°C for 30 s, 72°C for 45 s, followed by a final elongation at 72°C for 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, Alexander disease is classified into three subtypes: infantile, juvenile, and adult forms, based on the age at disease onset. Recently, GFAP mutations have been reported in various forms of Alexander disease Aoki et al 2001;Rodriguez et al 2001;Shiroma et al 2001;Gorospe et al 2002;Li et al 2002;Meins et al 2002;Namekawa et al 2002;Probst et al 2003;Sawaishi et al 2002;Shiihara et al 2002;Shiroma et al 2003;Suzuki et al 2004) and we have identified juvenile and adult forms of Alexander disease with three different GFAP mutations: V87G (Okamoto et al 2002), R88C (Nobuhara et al 2004) and R416W (Kinoshita et al 2003). To date, there had been few reports investigating the properties of mutant GFAP (Li et al 2005;Hsiao et al 2005;Perng et al 2006).…”
Section: Introductionmentioning
confidence: 84%